PENGARUH PENAMBAHAN LENGKUAS MERAH (Alppinia purpurata) TERHADAP KUALITAS DENDENG SAYAT IKAN BANDENG (Chanos chanos) SELAMA PENYIMPANAN - Rahmah, Rahmah; Wijaya, Muhammad; Mustarin, Amirah (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aimed to determine the effect of adding red galangal (Alppinia purpurata) to chemical, microbiological, and organoleptic qualities during storage.The type of this research is a quantitative research with experimental approaches and designed using completely randomized factorial design consist of two factors, namely factor A was the addition of galangal (control, 3%, 5%, and 7%) and factor B was the long of storage (0 day,  10 day, 20 day, 30 day) at room temperature. The number of  treatmented was tested  that as much as 16 treatments combinations. Each  treatment combination was repetition at 3 times to obtain 48 units experiment The The parameters observed in this research were water content, fat content, microbial colony count (ALT), sensory test of aroma and  appearance  of hedonic, texture, and  taste of  jerky the fish milkfish. Data were analyzed by  variance analysis techniques (ANOVA) and continued by duncan test. The best treatment was  jerky of milkfish  fish   with the addition of galangal 7% during storage that was the highest addition of galangal treatment. As long as the storage of test parameters decreases with time of storage. The treatment of the addition of galangal 7% was the best of product because it could still maintain the physical properties of the appearance, texture, aroma and taste of jerky the fish milkfish until the storage of the 10 day